Potency of Ethanol Extracts of Palm Seeds (Phoenix dactylifera L.) as Antidiabetic with Inhibition Kinetics Parameter - Lisa Giovanny; Faliha Arinda Lestari; Nurul Marfira; Laksmi Ambarsari; Siti Warnasih (IPB University, 2019)
Dates seeds are one of the byproducts of the date palm juice industry which has the potential for further processing. Dates seeds contain active compounds that are known to have ability to inhibit αglucosidase. This study aims to measure the activity of 70% ethanol extract and the fraction of date palm seeds with a mechanism in inhibiting αglucosidase. The measurement of inhibitory activity was carried out by extracting date palm seeds using 70% water and ethanol. The extraction product is then fractionated with n-hexane, ethyl acetate, n-butanol, and water. Then the total phenolic and flavonoid calculations were calculated for each extract and fraction. Measurement of α-glucosidase inhibition activity was measured based on reaction of substrate to enzyme by the addition of inhibitors. The results showed that the ethanolextract had the highest total phenolic and flavonoid, which were 76.86 mg GAE / g and 21.19 mg QE / g, respectively. n-hexane fraction have the best inhibitory activity seen from the IC50 value, which is 12.69 mg/L. The kinetics of inhibition of 70% ethanol extract of date palm seeds are mixed inhibition. Keywords: α-glucosidase, date seeds, flavonoids, kinetic inhibition, phenolics